1970
DOI: 10.1002/1097-0142(197002)25:2<436::aid-cncr2820250223>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Malignant melanoma of childhood.A clinicopathologic study and a report of 12 cases

Abstract: Twelve cases of malignant melanoma of childhood were collected from the pathology files of Memorial and James Ewing Hospitals covering a 40‐year period from 1928 to 1968. All of these cases had documented evidence of metastatic disease; 4 have survived longer than 5 years, and 2 of these are alive and well more than 15 years after therapeutic regional lymph node dissection. Clinical and pathologic findings in these cases are summarized, and a brief historical review is included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

1976
1976
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(15 citation statements)
references
References 30 publications
0
14
1
Order By: Relevance
“…It has been stated that one third of childhood melanoma arise from CGPN (11). This study, as well as other studies in the literature (25)(26)(27)(28), did not confirm this statement (Table 5). Using questionnaires, Ontario Cancer Registry data and a retrospective clinical review, only a single case of malignant melanoma arising from CGPN was identified during the past 15 years in Ontario, indicating the rarity of this condition.…”
Section: Discussioncontrasting
confidence: 82%
“…It has been stated that one third of childhood melanoma arise from CGPN (11). This study, as well as other studies in the literature (25)(26)(27)(28), did not confirm this statement (Table 5). Using questionnaires, Ontario Cancer Registry data and a retrospective clinical review, only a single case of malignant melanoma arising from CGPN was identified during the past 15 years in Ontario, indicating the rarity of this condition.…”
Section: Discussioncontrasting
confidence: 82%
“…These nevi follow a benign course, thus encouraging the misconception of a benign evolution of malignant melanoma in children. Malignant melanoma in children is capable of metastasis and may follow an aggressive pattern [4]. The connection between adult risk factors such as inability to tan or suering sunburn accompanied by blisters on the one hand and the development of childhood malignant melanoma on the other has not been proven [11].…”
Section: Discussionmentioning
confidence: 99%
“…Most cases have been reported in adults, but cases in young chil¬ dren have been documented. 16,73,74 Although melano¬ mas may arise de novo, they are more commonly asso¬ ciated with a precursor cellular blue nevus, which may be congenital (Figure 9). Because of the rarity of the event and the small number of published cases, the rate of malignant transformation of cellular blue nevi is un¬ known.74 Nevus spilus is a light brown-pigmented, circum¬ scribed macule in which darker-pigmented, raised or flat, lentigolike elements are present (Figure I O).…”
Section: On Other Melanocytic Nevimentioning
confidence: 99%
“…12,16,29,37,73,117 Currently, the same ex¬ cision margin criteria used for MM in adults are applied to childhood MM.12,39 Clinically suspected regional lymph nodes should also be removed.29,39,73 Regional lymph node dissection in the absence of clinically involved nodes re¬ mains controversial. 29,39,73,117'119 Besides surgery, the main alternative therapeutic meth¬ ods for MM include chemotherapy, radiotherapy, and im¬ munotherapy.…”
Section: Treatment and Preventionmentioning
confidence: 99%
See 1 more Smart Citation